solve this full

Asked by as9247555 | 19th May, 2020, 08:02: AM

Expert Answer:

Question: If pth term of a HP is qr and its qth term is pr then its rth term will be pq.
Proof:

Let H.P. be 1/a , 1/(a+d) , 1/(a+2d),....

Given a+(p-1)d = 1/qr

and a+(q-1)d = 1/pr

Solving for a and d we get a = -1/pqr  and d = 1/pqr

Therefore, a+(r-1)d= -1/pqr + (r-1)(-1/pqr) = 1/pq

Hence, the rth term of H.P. will be 1/(a+(r-1)d) = pq

Answered by Renu Varma | 19th May, 2020, 09:38: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.